2005
DOI: 10.1126/science.1116269
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure of a Mammalian Voltage-Dependent Shaker Family K + Channel

Abstract: Voltage-dependent potassium ion (K+) channels (Kv channels) conduct K+ ions across the cell membrane in response to changes in the membrane voltage, thereby regulating neuronal excitability by modulating the shape and frequency of action potentials. Here we report the crystal structure, at a resolution of 2.9 angstroms, of a mammalian Kv channel, Kv1.2, which is a member of the Shaker K+ channel family. This structure is in complex with an oxido-reductase beta subunit of the kind that can regulate mammalian Kv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

76
2,093
10
5

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 2,053 publications
(2,199 citation statements)
references
References 52 publications
76
2,093
10
5
Order By: Relevance
“…For the crystals of ICMT alone, two point mutations of surface residues were introduced to improve crystallizability (G151A and E154A). Transformation into P. pastoris , expression, and cryo-lysis were performed as previously described 27 .…”
Section: Methodsmentioning
confidence: 99%
“…For the crystals of ICMT alone, two point mutations of surface residues were introduced to improve crystallizability (G151A and E154A). Transformation into P. pastoris , expression, and cryo-lysis were performed as previously described 27 .…”
Section: Methodsmentioning
confidence: 99%
“…In the case of the voltage-gated K + channel (Kv), electrophysiological studies with toxin blockers showed the functional unit to be a tetramer 11 , a finding that was confirmed by X-ray crystallography [12][13][14][15] . Assembly of the four subunits into the tetrameric channel forms the permeation pathway in the centre.…”
mentioning
confidence: 89%
“… a–i , Pairwise superposition of the pore domain in hTRPV6 with ( a ) rat TRPV1 18 (PDB ID: 5IRX; RMSD = 2.065 Å), ( b ) rabbit TRPV2 21 (PDB ID: 5AN8; RMSD = 3.757 Å), ( c ) rat TRPV2 24 (PDB ID: 5HI9; RMSD = 4.399 Å), ( d ) human TRPA1 23 (PDB ID: 3J9P; RMSD = 1.429 Å), ( e ) human PKD2 25 (PDB ID: 5T4D; RMSD = 2.676 Å), ( f ) KcsA from Streptomyces lividans 47 (PDB ID: 1BL8; RMSD = 2.708 Å), ( g ) MthK from M. thermautotrophicum 48 (PDB ID: 1LNQ; RMSD = 2.947 Å), ( h ) rat Shaker 49 (PDB ID: 2A79; RMSD = 2.487 Å) and ( i ) rat GluA2 AMPA-subtype iGluR 28 (PDB ID: 5WEO; RMSD = 2.044 Å). j , Sequence alignment for the pore region of human TRPV3–6, TRPA1 and PKD2, rat TRPV1, 2, 6, Shaker and GluA2, rabbit TRPV2 and bacterial K + channels KcsA and MthK.…”
Section: Extended Datamentioning
confidence: 99%